Epizootological information of infectious hepatitis of dogs and comparative estimation of efficiency of charts of treatment in LTD. «Vetservis» Poltava - Коне, М. С.; Петренко, А. А.; Цибулько, О. О. (Scientific Progress & Innovations, 2012)
Studied age-dependent and pedigree sensitiveness, seasonality and dynamics of display of infectious hepatitis of dogs in the conditions of veterinary clinics of LTD «Vetservis» Poltava. The various charts of treatment of infectious hepatitis are offered for dogs. The new medical chart of infectious hepatitis of dogs is developed. It is set that infectious hepatitis is more frequent registered among dogs in age from one to two years (25,7 % cases). Not thoroughbred animals more feel like a disease (25,6 %). Disease has the expressed seasonality which shows up more frequent cases of origin of hepatitis in a spring-summer period. The our new chart of treatment has 100 % efficiency.